2018
DOI: 10.1016/j.molcel.2018.01.009
|View full text |Cite
|
Sign up to set email alerts
|

OTUD4 Is a Phospho-Activated K63 Deubiquitinase that Regulates MyD88-Dependent Signaling

Abstract: Ubiquitination is a major mechanism that regulates numerous cellular processes, including autophagy, DNA damage signaling, and inflammation. While hundreds of ubiquitin ligases exist to conjugate ubiquitin onto substrates, approximately 100 deubiquitinases are encoded by the human genome. Thus, deubiquitinases are likely regulated by unidentified mechanisms to target distinct substrates and cellular functions. Here, we demonstrate that the deubiquitinase OTUD4, which nominally encodes a K48-specific deubiquiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
85
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 37 publications
0
85
0
Order By: Relevance
“…Here, ATX3 assists the p97‐dependent substrate extraction of the substrates from the ER or chromatin by trimming their associated ubiquitin chains to allow timely processing of the substrates (extraction from ER or chromatin), most probably through the central pore of p97 in a manner recently described (Bodnar & Rapoport, ). The different roles of ATX3 on RNF8 could be potentially regulated by two different ubiquitin chain types on RNF8 (K48 and K63; Fig EV1D) and/or the phosphorylation status of ATX3 (Matos et al , ), as recently described for the DUB OTUD4 (Zhao et al , ). Unphosphorylated OTUD4 trims K48‐Ub signals from alkylation DNA repair proteins and thus counteracts their proteasomal degradation.…”
Section: Discussionmentioning
confidence: 63%
“…Here, ATX3 assists the p97‐dependent substrate extraction of the substrates from the ER or chromatin by trimming their associated ubiquitin chains to allow timely processing of the substrates (extraction from ER or chromatin), most probably through the central pore of p97 in a manner recently described (Bodnar & Rapoport, ). The different roles of ATX3 on RNF8 could be potentially regulated by two different ubiquitin chain types on RNF8 (K48 and K63; Fig EV1D) and/or the phosphorylation status of ATX3 (Matos et al , ), as recently described for the DUB OTUD4 (Zhao et al , ). Unphosphorylated OTUD4 trims K48‐Ub signals from alkylation DNA repair proteins and thus counteracts their proteasomal degradation.…”
Section: Discussionmentioning
confidence: 63%
“…41,42 However, phosphorylation at the catalytic domain of OTUD4 at Ser202/ 204 activates its K63-specific DUB activity, which targets MyD88 for deubiquitination and thereby downregulates TLR-mediated NF-κB activation. 43 In addition, OTUD4 promotes the repair of DNA alkylation damage in a manner independent of its DUB activity. 41 The K48-specific DUB activity of OTUD4 and the target(s) and the related physiological or pathological significance of such an activity remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…MyD88 could be ubiquitinated by either K48 or K63-linked ubiquitination[1013]. To investigate the molecular mechanisms of SPOP-mediated degradation of MyD88, we transfected vectors expressing HA-tagged K48 or K63-linked ubiquitin into chicken DF1 cells, and found that overexpression of chSPOP enhanced the K48-linked rather than the K63-linked ubiquitination of chMyD88 (Fig 3A, lanes 3,4).…”
Section: Resultsmentioning
confidence: 99%
“…Excessive inflammation and the production of proinflammatory cytokines and interferons resulting from the misregulation of MyD88 signaling are detrimental to health and might lead to pathological damage, such as cancer and autoimmune diseases [2729]. Several mechanisms that regulate the activity of MyD88 have been revealed [913, 18]. For example, transforming growth factor-β induces the Smad6-dependent recruitment of E3 ubiquitin ligases Smurf1 and Smurf2 to MyD88, targeting them for proteasomal degradation and thereby displaying its anti-inflammatory function [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation